2021
DOI: 10.3390/nano11123235
|View full text |Cite
|
Sign up to set email alerts
|

Electrode–Electrolyte Interactions in an Aqueous Aluminum–Carbon Rechargeable Battery System

Abstract: Being environmentally friendly, safe and easy to handle, aqueous electrolytes are of particular interest for next-generation electrochemical energy storage devices. When coupled with an abundant, recyclable and low-cost electrode material such as aluminum, the promise of a green and economically sustainable battery system has extraordinary appeal. In this work, we study the interaction of an aqueous electrolyte with an aluminum plate anode and various graphitic cathodes. Upon establishing the boundary conditio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
(63 reference statements)
1
0
0
Order By: Relevance
“…Mechanistically, the electrolyte's concentration affects the ionic charge transfer through the IL-SEI by partially breaking this ex situ interface during the cell's operation, thereby forming a new (in situ) SEI. In agreement with Zhao et al and others, the optimal Al(OTF) 3 concentration for this system is 2 M. 19,20 Meanwhile, other teams have continued to use the IL-SEI approach to shed light on a number of different questions. For instance, working with an OTF-based electrolyte, Li et al found that the anion OTFparticipates in the Al solvation structure as [Al(H 2 O) 4 (OTF)] 2+ .…”
Section: Current Statussupporting
confidence: 81%
“…Mechanistically, the electrolyte's concentration affects the ionic charge transfer through the IL-SEI by partially breaking this ex situ interface during the cell's operation, thereby forming a new (in situ) SEI. In agreement with Zhao et al and others, the optimal Al(OTF) 3 concentration for this system is 2 M. 19,20 Meanwhile, other teams have continued to use the IL-SEI approach to shed light on a number of different questions. For instance, working with an OTF-based electrolyte, Li et al found that the anion OTFparticipates in the Al solvation structure as [Al(H 2 O) 4 (OTF)] 2+ .…”
Section: Current Statussupporting
confidence: 81%
“…In addition, different processing methods can obtain graphite-based materials with different properties. For example, pretreated graphite can produce flake graphite foam electrodes [86], supercritical drying method can obtain mesoporous reduced graphene oxide powder [88], using freezedrying synthesized can reduced graphene oxide [89]. Oxygen group functional groups on graphene sheets can improve wettability and thus increase charge storage, such as oxygen-rich layered porous graphene electrode materials with high specific surface areas [87].…”
Section: Carbonaceous Materialsmentioning
confidence: 99%